2017
DOI: 10.1080/10942912.2017.1303709
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of enzymes linked to type-2 diabetes and hypertension by essential oils from peels of orange and lemon

Abstract: This study was designed to evaluate and compare the interactions of essential oils from orange (Citrus sinensis [L.] Osbeck) and lemon (Citrus limon) peels on enzymes linked to type-2 diabetes (α-amylase and α-glucosidase) and hypertension (angiotensin-I-converting enzyme [ACE]). The essential oils were obtained from the peels by hydrodistillation and were passed over anhydrous sodium sulphate. The interaction of the oil on αamylase, α-glucosidase, and ACE activities was subsequently determined. The results re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 28 publications
2
28
0
2
Order By: Relevance
“…This has been attributed to insulin resistance induced stimulation of the angiotensin 1 receptor ( Tuck et al, 2004 ). Stimulation of the angiotensin 1 receptor activates the angiotensin 1 converting enzyme (ACE), thereby causing an elevated level of angiotensin II which is vasoconstrictive ( Oboh et al, 2017 ). The dose-dependent inhibition of ACE by the DCM fraction ( Figure 8 ), therefore indicates a protective effect against hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…This has been attributed to insulin resistance induced stimulation of the angiotensin 1 receptor ( Tuck et al, 2004 ). Stimulation of the angiotensin 1 receptor activates the angiotensin 1 converting enzyme (ACE), thereby causing an elevated level of angiotensin II which is vasoconstrictive ( Oboh et al, 2017 ). The dose-dependent inhibition of ACE by the DCM fraction ( Figure 8 ), therefore indicates a protective effect against hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme plays a very important role in regulating the potential of cell membrane and neuronal impulsiveness by readily pumping Na + and K + against the electrochemical gradient across the cell membrane (Wyse et al, ). Nevertheless, this enzyme is altered in neurodegenerative diseases such as Alzheimer’s and Parkinson’s disease (Oboh, Olasehinde, et al, ). Reducing Na + /K + ATPase activity causes a disruption in the sodium gradient, which brings about the release of neurotransmitters across the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…High angiotensin‐1‐converting enzyme (ACE) activity has been connected to hypertension, this is because it degrades bradykinins, a peptide that causes blood pressure to fall (a vasodilator) (Je, Park, Kim, & Ahn, ; Oboh, Olasehinde, et al, ). Inhibiting ACE activity by ethyl acetate fraction of S. macrocarpon leaves may have a great effect in lowering blood pressure and overall in the management of hypertension (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…More than 3,000 plants are known to produce essential oils of which approximately 300 are of commercial importance (Palazzolo, Laudicina, & Germanà, 2013). Studies on essential oils from aromatic plants showed that they exert a broad spectrum of bioactivity owing to the presence of volatile molecules such as terpenes and phenol-derived aromatic and aliphatic components (Adefegha, Olasehinde, & Oboh, 2017;Lawal & Ogunwande, 2013;Oboh, Olasehinde, & Ademosun, 2017). Studies on essential oils from aromatic plants showed that they exert a broad spectrum of bioactivity owing to the presence of volatile molecules such as terpenes and phenol-derived aromatic and aliphatic components (Adefegha, Olasehinde, & Oboh, 2017;Lawal & Ogunwande, 2013;Oboh, Olasehinde, & Ademosun, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…About 65% of the world's production of essential oils came from developing countries. Studies on essential oils from aromatic plants showed that they exert a broad spectrum of bioactivity owing to the presence of volatile molecules such as terpenes and phenol-derived aromatic and aliphatic components (Adefegha, Olasehinde, & Oboh, 2017;Lawal & Ogunwande, 2013;Oboh, Olasehinde, & Ademosun, 2017).…”
Section: Introductionmentioning
confidence: 99%